The Welfare State and Beyond : Success and Problems in Scandinavia - Heckscher, Gunnar, 1909-1987 (Book collections on Project MUSE., 1984)
The Welfare State and Beyond was first published in 1984. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. The welfare state emerged in a number of industrialized countries after the First World War as a middle ground between capitalism and socialism. The aim of architects of the welfare state was to abolish the injustices and hardships that accompanied capitalism and to do so without wholesale social or economic revolution. Establishment of the welfare.